DIAGNOSIS DAN PENATALAKSANAAN PNEUMONITIS HIPERSENSITIVITAS - Dary, I Wayan; Ngurah Rai, Ida Bagus (journal of internal medicine, 2008)
Hypersensitivity pneumonitis (HP), or extrinsic allergic alveolitis, is a group of immunologically mediated lung diseasesin which the repeated inhalation of certain finely dispersed antigens of a wide variety, mainly including organic particles or lowmolecular weight chemicals, provokes a hypersensitivity reaction with granulomatous inflammation in the distal bronchioles andalveoli of susceptible subjects. HP can be classified as acute, subacute, and chronic form. Clinically its presented as fever, fatique,myalgia, cough and shortness of breath after exposured and physical finding with fever, takipneu, diffuse rhales bibasal. Chestradiograph showed diffuse micronodular pattern or ground-glass appearance on lower and mid field lung only found on tenperse10%n of cases. HRCT can show more specific abnormalities of the lung. Lung function test describe restrictive type.Hystopathologic features are noncaseating granulomas, giant cells with a lot of nucleus, and mononuclear cells infiltration. Themost diagnostic criteria used is made by Richerson et al. the history and physical findings and pulmonary function tests indicatean interstitial lung disease, the X-ray film is consistent, there is exposure to a recognized cause, and there is antibody to thatantigen. Being an immune reaction in the lung, the most obvious treatment of HP is avoidance of contact with the offendingantigen. Systemic corticosteroids represent the only reliable pharmacologic treatment of HP but do not alter the long-term outcome.On the acute HP, prednisone administrate 1 mg/kgBW/day or its equivalent dose for 7 ? 14 days than tapering off foe 2 ? 6 weeks.